Integrating basketball skills learning into mathematics: an innovative model to improve skills and performance - Oki Candra; Wahyuni, Putri; Rahmadani, Ahmad; Parulian, Toktong; Dupri, Dupri; Putra, Jeki Purnama; Kamarudin, Harris Kamal (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Basketball skills learning has focused more on physical and technical aspects without considering quantitative analysis-based approaches such as mathematics, which can provide a deeper understanding of movement strategies and effectiveness. This study aimed to develop and test the effectiveness of a mathematics-based basketball skills learning model to improve students’ understanding of movement concepts and playing performance. It used a research and development (R&D) method with a quasi-experimental approach, involving students as research subjects and measuring the model’s effectiveness through validity tests, practicality, and improvement of student skills before and after implementing the model. The results of the effectiveness test of the learning model through pretest and posttest showed increased skills in three main aspects: dribbling, passing, and shooting. In dribbling skills, the percentage of achievement increased from 12.84% in the pretest to 20.86% in the posttest. Passing experienced a substantial increase from 27.26% to 41.92%, while shooting also increased from 4.11% to 9.11%. These results indicate that the applied math-based learning model improves students’ basic basketball skills. Developing a mathematics-based learning model in basketball positively contributes to the effectiveness of sports skills learning, so it is recommended to be applied in the physical education curriculum to improve students’ cognitive understanding and motor skills.